2018
DOI: 10.1515/nleng-2017-0055
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of non-Newtonian boundary layer flow of nanofluid past a semi-infinite vertical plate with partial slip

Abstract: An analysis of this paper is examined, two-dimensional, laminar with heat and mass transfer of natural convective nanofluid flow past a semi-infinite vertical plate surface with velocity and thermal slip effects are studied theoretically. The coupled governing partial differential equations are transformed to ordinary differential equations by using non-similarity transformations. The obtained ordinary differential equations are solved numerically by a well-known method named as Keller Box Method (KBM). The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…It was found that when the flow pressure is low, the slip boundary condition is necessary. A slip condition on stretching or shrinking surfaces is used by several researchers [15][16][17][18][19]. Ramaya et al [15] analyzed the nanofluids through a stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that when the flow pressure is low, the slip boundary condition is necessary. A slip condition on stretching or shrinking surfaces is used by several researchers [15][16][17][18][19]. Ramaya et al [15] analyzed the nanofluids through a stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Extend the work of Raju et al 7 and Tamoor et al 8 to MHD fluid flow on moving over the porous stretching plate with Casson fluid using the Kellarbox technique is discussed by Ullaha et al 9 Amanulla et al 10 discussed thermal and nanoliquid flow across a vertical plate, and they discovered that the slip parameter reduces concentration profiles. The physical problems of MHD and complexity of solutions of nonlinear partial differential equations (PDEs) over the plate, moving plate, with ramped wall temperature, rotating disc, exponentially porous stretching plate, and chemical molecular diffusivity are discussed in Amanullah et al, 10 Onyejekwe, 11 Kataria and Patel, 12 Alreshidi et al, 13 Reddy et al, 14 and Haq et al, 15 respectively. Nowadays many industries are facing the complexity of computing the thermal diffusion and the diffusion-thermo in energy flux caused by concentration differences.…”
Section: Introductionmentioning
confidence: 99%
“…Casson uid model is one of the non-Newtonian uids which models uids such as jelly, honey, fruit juices, soup, and blood etc. Casson uid is a shear-thinning uid exhibiting yield stress and which has in nite viscosity at a low shear rate and zero viscosity at the in nity shear rate; RamReddy et al [15] and Amanulla et al [16]. In other words, Casson uid behaves like a solid when yield stress is more than the shear stress but behaves like a liquid and ows when the yield stress is less than the shear stress.…”
Section: Introductionmentioning
confidence: 99%